2022
DOI: 10.1073/pnas.2111537119
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis triggers spatially restricted neutrophil-mediated vascular damage during lung ischemia reperfusion injury

Abstract: Significance Intravital imaging, oxidative lipidomics, and a transplant model were used to define mechanisms that regulate neutrophil recruitment into lungs during ischemia reperfusion injury, a clinically relevant form of sterile inflammation. We found that early neutrophil-mediated damage is largely confined to the subpleural vasculature, a process that is orchestrated by a spatially restricted distribution of nonclassical monocytes that produce chemokines following necroptosis of pulmonary cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 70 publications
0
47
0
Order By: Relevance
“…We have previously reported that ischemia-reperfusion injury is inherent to lung transplantation and is dependent on the influx of host neutrophils into the transplanted lung through retained donor-origin pulmonary intravascular nonclassical monocytes ( 22 , 23 ). To determine whether LRAs can independently induce lung graft dysfunction, we used lungs from murine Nur77 –/– ( Nr4a1 –/– ) donors, which lack nonclassical monocytes and do not experience neutrophil-mediated ischemia-reperfusion injury, as we previously reported ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that ischemia-reperfusion injury is inherent to lung transplantation and is dependent on the influx of host neutrophils into the transplanted lung through retained donor-origin pulmonary intravascular nonclassical monocytes ( 22 , 23 ). To determine whether LRAs can independently induce lung graft dysfunction, we used lungs from murine Nur77 –/– ( Nr4a1 –/– ) donors, which lack nonclassical monocytes and do not experience neutrophil-mediated ischemia-reperfusion injury, as we previously reported ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using intravital imaging, oxidative lipidomics, and transplant models, Li et al (114) demonstrated that TLR4 signaling and downstream NOX4 expression in vascular endothelial cells during lung I/R mediate neutrophil recruitment to the lungs and increase NET formation. The knockdown of TLR4 expression in vascular endothelial cells results in decreased neutrophil infiltration and NETosis (114). Treatment with DNase I reduces lung neutrophil extravasation and subpleural NET formation, thus improving graft function (114).…”
Section: Extracellular Traps In Lung Ischemia Reperfusion Injurymentioning
confidence: 99%
“…( 114 ) demonstrated that TLR4 signaling and downstream NOX4 expression in vascular endothelial cells during lung I/R mediate neutrophil recruitment to the lungs and increase NET formation. The knockdown of TLR4 expression in vascular endothelial cells results in decreased neutrophil infiltration and NETosis ( 114 ). Treatment with DNase I reduces lung neutrophil extravasation and subpleural NET formation, thus improving graft function ( 114 ).…”
Section: Extracellular Traps In Organ Ischemia Reperfusion Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…The critical function of chemokines is to manage the migration of hemameba to their specific position during equilibrium process when the process goes disease disorders. Chemokines directionally induce chemotaxis of nearby reactive cells through promoting proliferation of vascular endothelial cells and angiogenesis ( Li et al, 2022 ). Vascular endothelial cells, chemokine (C-X-C motif) ligand 12 (CXCL12)-rich reticular cells, and mesenchymal stromal cell-regulated chemokines, cytokines, and cell surface adhesion molecules have been identified as microenvironmental cells in neoplastic hematopoiesis ( Kaushansky and Zhan, 2018 ).…”
Section: Part Three: Changes In Vascular Endothelial Nichesmentioning
confidence: 99%